2009
DOI: 10.1164/rccm.200808-1224oc
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the Lung Parenchyma Early in Life

Abstract: Rationale: Early in life, lung growth can occur by alveolarization, an increase in the number of alveoli, as well as expansion. We hypothesized that if lung growth early in life occurred primarily by alveolarization, then the ratio of pulmonary diffusion capacity of carbon monoxide (DL CO ) to alveolar volume (V A ) would remain constant; however, if lung growth occurred primarily by alveolar expansion, then DL CO /V A would decline with increasing age, as observed in older children and adolescents. Objectives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 19 publications
2
42
0
2
Order By: Relevance
“…Early in life, lung volume is thought to increase primarily by the addition of alveoli, while in older children, lung volume increases primarily by the expansion of existing alveoli. We have previously demonstrated that the diffusing capacity of the lung for carbon monoxide (DLCO) and alveolar volume (VA) increase with increasing body length in infants and toddlers; however, the ratio of DLCO/VA remained constant with lung growth early in life [1]. These physiological findings are consistent with lung growth occurring by the addition of alveoli, with comparable increases in alveolar surface area and VA.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Early in life, lung volume is thought to increase primarily by the addition of alveoli, while in older children, lung volume increases primarily by the expansion of existing alveoli. We have previously demonstrated that the diffusing capacity of the lung for carbon monoxide (DLCO) and alveolar volume (VA) increase with increasing body length in infants and toddlers; however, the ratio of DLCO/VA remained constant with lung growth early in life [1]. These physiological findings are consistent with lung growth occurring by the addition of alveoli, with comparable increases in alveolar surface area and VA.…”
Section: Introductionsupporting
confidence: 57%
“…• adjusting for somatic size [1,20]. We did find a sex difference for VC, but not for DM, after adjusting for body length and race.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Beginning at 35 weeks after conception and continuing for up to 8 years after birth, the alveolar stage of lung development is marked by the sequential division of larger airspaces into smaller ones by secondary alveolar septa (1,2). From term birth until adulthood, the 5-fold increase in the number of alveoli and the 20-fold increase in alveolar surface area are critical in meeting the increasing oxygenation and ventilation needs of human growth and activity (2,3).…”
mentioning
confidence: 99%
“…From term birth until adulthood, the 5-fold increase in the number of alveoli and the 20-fold increase in alveolar surface area are critical in meeting the increasing oxygenation and ventilation needs of human growth and activity (2,3). Premature birth, exposure to high concentrations of inspired oxygen, and mechanical ventilation lead to impaired alveolar development and chronic lung disease (4).…”
mentioning
confidence: 99%